Perancangan Sekolah Alam di Klender Jakarta Timur Dengan Konsep Arsitektur Tropis - Dimas Setyaji Nugraha; Putri Suryandari (MAESTRO, 2019)
Nature School Klender is an Educational facility in East Jakarta that accommodates teaching and learning activities set in nature with high school and kindergarten levels, in this School of Nature students are given the following knowledge: Learn to know nature further, train students' independence, students are given understanding about how to maintain a good environment, so students understand the environment around their homes and also in schools, the facilities provided in this school start from the Outdoor, Playgrond, Plantation, Camping grond, fish ponds and research laboratories. The School of Nature which is insulated in Klender East Jakarta was taken as a synthesis in the concept of planning and design. This development plan seeks to provide a building function that accommodates natural-themed teaching and learning activities with a tropical architectural approach. The concept of applied tropical architecture seeks to unite climate conditions in Indonesia with their application to land and buildings